Fenomena dan Tantangan Terkait Kejahatan Cyber oleh dan terhadap Anak di Indonesia - Sirait, Yohanes Hermanto (Zenit, 2015)
Positively, technology development in combination with information, yields economic growth that, in turn, is necessary to generate further advances in human development. Information technology in some respect helps humans for having better education and information with itscharacter of transboundary. However, we cannot deny that negatively technology information couldbecome a problem if users cannot use it properly, especially children or young people. This researchis done to examine the phenomena and challenges on cyber crimes done by – and to children inIndonesia. This research also examines the policy on security and protection of children from the misuse of information technology through Internet.Keywords: cyber crime, children, Internet, security, and protection